ASP Flooding: Theory and Practice Progress in China - Hu Guo; Yiqiang Li; Fuyong Wang; Zhaoyan Yu; Zhiwei Chen; Yansheng Wang; Xian Gao (Journal of Chemistry)
In low oil price era, it seems that ASP flooding has little market. However, ASP progress in China shows that ASP flooding is good technology to help oil companies thrive and make profit. Since 2014, ASP flooding has entered industrial application in Daqing oilfield. ASP flooding production in 2015 is 3.5 million ton, 9% of the oilfield’s total production of Daqing oilfield. There are 22 ASP flooding blocks in Daqing, containing 7231 wells and 3 are new blocks in 2016. Obviously, more and more ASP flooding is being carried out. Another large ASP flooding field test in high temperature (80°C) in Henan oilfield has got staged incremental oil recovery of 7.7%. Latest theory and application in ASP flooding in China are reviewed to help ASP flooding go from success to more application. Weak alkali is better than strong alkali ASP flooding. Relation between viscosity and IFT is discussed. This paper also explains why weak alkali ASP flooding is promoted in Daqing after 12 field tests on strong alkali one. ASP flooding can be a great help to survive low oil price.